Pelatihan Metode Seleksi Dan Perkawinan Untuk Pengembangan Sapi Potong Bagi Warga Kecamatan Paguyaman Dan Wonosari Provinsi Gorontalo - Ilham, Fahrul; Bahri, Syamsul; Ervandi, Mohamad; Mukhtar, Muhammad (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Community Service (PPM) aims to increase the knowledge and skills of residents in Paguyaman and Wonosari Districts regarding selection and mating methods for beef cattle. This PPM activity was carried out on 15 and 16 September 2023 in Paguyaman District, Boalemo Regency, precisely at the Unit Pelaksana Teknis Daerah (UPTD) Pengembangan Ternak Dinas Pertanian Provinsi Gorontalo. Participants in the activity are beef cattle breeders who work as cattle breeders from the Paguyaman and Wonosari Districts. This PPM activity consists of 3 stages, including preparation, implementation, and evaluation stages. The activity method carried out at the implementation stage is counseling by means of lectures and discussions with participants. The results obtained after all stages of activities were carried out show that training on selection and mating methods for beef cattle development for cattle breeders in Paguyaman and Wonosari Districts has been carried out well and as expected. The response of breeders during the training activities was quite good, as indicated by the presence of all invited participants, the creation of discussions and exchange of experiences between fellow participants, and the submission of questions by training activity participants during discussion sessions. This training activity will be maximized if recording beef cattle production from breeders is available so that methods and selection that suit the breeders' real conditions can be carried out.